Financing difficulties facing small projects and the prospects for their solutions (an applied study on Libya) (Economic studies journal, 2020)
This study aims to investigate difficulties faced small business to obtain finance, and also attempts to identify reasons for why small business do not obtain sufficient finance, and the best way to increase finance for small business To achieve the objectives of study, this paper used descriptive methodology, and a questionnaire was distributed to collect primary and secondary data. The results of study showed that small business are more able and efficient than large enterprises in term jobs offer, manage its investments and the finance is the main problem faced small business. The study suggest that we need to establish governmental agency for small business, existing of strategic planning, use Islamic finance, and development of financial market to boost growth of small business.
Keywords: Key words: small business, collateral, finance leasing, finance difficulties